2020
DOI: 10.1088/1748-9326/abc4fb
|View full text |Cite
|
Sign up to set email alerts
|

Vascular plant species response to warming and elevated carbon dioxide in a boreal peatland

Abstract: Peatlands store a significant amount of terrestrial organic carbon in plant biomass and soils. The Spruce and Peatland Responses Under Changing Environments (SPRUCE) project is a warming and elevated carbon dioxide (eCO2) experiment designed to test how the carbon sequestration and storage capacity of peatland ecosystems will respond to climate change. Here, we report changes in the vascular plant community that have occurred during the first five years of SPRUCE. We tracked species composition, diversity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 58 publications
2
34
1
Order By: Relevance
“…It is our hope that our study has shed some light on what may occur as we now transition from the Holocene to the Anthropocene. We realize that a myriad of other factors in addition to temperature will affect peatland carbon storage including water table changes (Roulet et al, 1993), fires (Flanagan et al, 2020;Turetsky et al, 2015), and vegetation changes such as increasing shrubification and Sphagnum loss (Malhotra et al, 2020;McPartland et al, 2020;Norby et al, 2019). In addition, peat may be buried under mineral soils with changing climate and thus preserved for periods of time on the order of hundreds of thousands of years (Treat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is our hope that our study has shed some light on what may occur as we now transition from the Holocene to the Anthropocene. We realize that a myriad of other factors in addition to temperature will affect peatland carbon storage including water table changes (Roulet et al, 1993), fires (Flanagan et al, 2020;Turetsky et al, 2015), and vegetation changes such as increasing shrubification and Sphagnum loss (Malhotra et al, 2020;McPartland et al, 2020;Norby et al, 2019). In addition, peat may be buried under mineral soils with changing climate and thus preserved for periods of time on the order of hundreds of thousands of years (Treat et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary isotopic measurements imply that a significant fraction of carbon assimilated by the moss may come from subsurface-respired CO 2 (i.e., CO 2 with older 14 C signatures predating bomb carbon that can only be sourced from deeper peat; Hanson et al, 2017). However, the observed elevated CO 2 response is smaller than simulated (Hanson et al, 2020). Understanding the drivers of elevated CO2 response or lack thereof is a key topic for future work.…”
Section: Predicted Warming and Elevated Co 2 Concentration Response Uncertaintiesmentioning
confidence: 97%
“…Norby et al (2019) investigated different Sphagnum species at the same site and reported there was no support for the hypothesis that species more adapted to dry conditions (e.g., S. magellanicum and Polytrichum mainly on hummocks) would be more resistant to the stress and would increase in dominance, and both hummock and hollow Sphagnum decline with warming despite the differences between them. This declining trend may be in part due to increased shading from the shrub layer which expands with warming (McPartland et al, 2020).…”
Section: Predicted Warming and Elevated Co 2 Concentration Response Uncertaintiesmentioning
confidence: 99%
“…In that study water potential of the shrubs was more variable but also indicated midday water stress for some plants, especially Chamaedaphne calyculata (−1.5 to −2.0 MPa) and Rhododendron groenlandicum (previously Ledum groenlandicum ; −1.4 to −1.9 MPa), while Kalmia polifolia and Vaccinium angustifolium peaked higher (−1.2 to −1.6 MPa). Along with the Sphagnum moss groundcover, the species‐specific responses of this community to drier or hotter conditions will shape southern boreal peatland composition (McPartland et al, 2020; Norby et al, 2019) and productivity (Hanson, Griffiths, et al, 2020) in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Increased productivity by some species may lead to decline of other species, such as exhibited by shrub expansion under whole ecosystem warming (McPartland et al, 2019) at the expense of Sphagnum spp. (Norby et al, 2019) and forbs (McPartland et al, 2020). Thus, knowledge of species‐specific responses to peatland warming and the underlying mechanisms is necessary to assess the trajectory of peatland ecosystems in the future.…”
Section: Introductionmentioning
confidence: 99%